Implementation Design Thinking in Google Sites with TaRL-Approach to Improve Mathematical Problem-Solving Skills - Harpeningtyas, Rinayanti Budi; Nizaruddin, Nizaruddin; Dwijayanti, Ida (Universitas Wiralodra, 2025)
The 21st century requires individuals toahaveatheaabilityato think_comprehensively, especially in criticalaandacreative_thinking. The result of the PISA study show that the literacy skills of Indonesian student are still relatively low, including in terms of numeracy or mathematical problem solving. Preliminary data shows that most students have a